Application of Internent in the Information Management at the Ministry of Works and Transport-Entebe - Vivian, Susan Eton (Kampala : Uganda Christian University, 2010)
Discriptive Cataloguing Uganda Christian University BLIS
Includes Appendix and References
Keywords: Information Management